1989
DOI: 10.1002/j.1460-2075.1989.tb03395.x
|View full text |Cite
|
Sign up to set email alerts
|

Studying the structure of the intracellular moiety of the insulin receptor with a kinase-splitting membranal proteinase.

Abstract: A kinase‐splitting membranal proteinase specifically clips the cytoplasmic moiety of the insulin receptor beta‐subunit (95 kd) to yield an 84‐kd fragment. Using antibodies against different domains in the receptor, cleavage is shown to remove an 11‐kd ‘tail’ (rooted at the C‐terminal end of the kinase domain) which includes tyrosines 1316 and 1322. This cleavage impairs the ability of the clustered tyrosines 1146, 1150 and 1151 to undergo autophosphorylation. Nevertheless, the clipped beta‐subunit is as active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It attracted our attention not merely because it selectively inactivates PKA but also because of the specificity with which it clips off the carboxyl terminus tail of the C subunit of PKA. In addition, KSMP was found to clip off the carboxyl terminus tail of two other important kinases: the epidermal growth factor receptor kinase (9) and the insulin receptor kinase (10). In all three kinases, the cleavage was shown to be conformation-dependent (2, 7, 9, 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It attracted our attention not merely because it selectively inactivates PKA but also because of the specificity with which it clips off the carboxyl terminus tail of the C subunit of PKA. In addition, KSMP was found to clip off the carboxyl terminus tail of two other important kinases: the epidermal growth factor receptor kinase (9) and the insulin receptor kinase (10). In all three kinases, the cleavage was shown to be conformation-dependent (2, 7, 9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of these studies, it was found that KSMP also clips off specifically the carboxyl-terminal end of the epidermal growth factor receptor and the insulin receptor (9,10), again in a conformation-dependent manner. Somewhat unexpectedly at the time, it was found that KSMP is an ecto-enzyme, i.e.…”
mentioning
confidence: 99%
“…The evidence supporting the importance of hydrophobic amino acid residues is summarized in the following. (i) The protein substrate (C-subunit) with which KSMP was originally discovered (1-3), as well as the EGF-and insulin-receptor kinases (7,10,11), contain hydrophobic amino acid residues within or adjacent to their cluster of acidic amino acids. (ii) The dye 1-anilino-8-naphthalenesulfonate, which is known to bind to hydrophobic sites in proteins, inhibits the cleavage of the Csubunit by KSMP (45).…”
Section: Use Of Synthetic Peptides Derived From the C-subunit To Estamentioning
confidence: 99%
“…Interestingly, two other kinases, the EGF-and the insulin-receptor kinases (which share certain sequence homology with the C-subunit (9)) were also shown to undergo a specific and conformation-dependent cleavage by KSMP (6,[10][11][12]. In both receptor kinases, it was shown that the KSMP cleavage occurs at the carboxyl-terminal part of the molecules.…”
mentioning
confidence: 99%
“…boxy-terminus tail of C (327FDDYEEEEI335) is the major biorecognition element for KSMP, since antiidiotypic monoclonal antibodies against a copolymer containing clusters of E and Y were found to inhibit KSMP [12]. A similar conformation-dependent cleavage by KSMP was shown to occur also in two other protein kinases which contain such clusters of acidic amino acids at their carboxy-terminus tail --the EGF receptor kinase, and the insulin receptor kinase [13,14], raising the possibility that the malleable tails at the carboxy terminus of these kinases may play an important role in their biorecognition and regulation [13][14][15][16]. This paper describes the preparation and characterization of anti-head and anti-tail antibodies against distinct epitopes in C, and their use in the specific identification of PKA and in the assay of KSMP by the determination of C and C'.…”
Section: Introductionmentioning
confidence: 99%